Decomposition Characteristics of SF(6) under Flashover Discharge on the Epoxy Resin Surface - Wen, Hao (Materials (Basel), 2019)
In this paper, the flashover discharging experiment was carried out on epoxy resin surface in an SF(6) atmosphere under pin-plate electrodes, with the electrodes distance from 5 mm to 9 mm. The concentration of seven characteristic gases was detected, indicating that the concentration of SOF(2) and CF(4) was the two highest, followed by SO(2), CO(2), SO(2)F(2), CS(2), and H(2)S. Based on the changes in the concentration of the characteristic gases, a preliminary rule was proposed to predict the occurrence of flashover discharge on epoxy resin: When the concentration of SOF(2) reaches twice of CF(4) concentration, and the total concentration of both SOF(2) and CF(4) is much higher than that of H(2)S, a possible flashover discharge on the epoxy resin surface in SF(6)-infused electrical equipment occurs. Through the simulation of decomposition of epoxy resin, it has been revealed that H(2)O has different generation paths that can facilitate the formation of SOF(2), finally influencing the concentration variation of the seven characteristic gases.